Quantifying Blowdown Disturbance in Overstory Retention Patches in Managed Nothofagus pumilio Forests with Variable Retention Harvesting - Martínez Pastur, Guillermo José (2024)
The natural resilience of the forests to face impacts of blowdown damages was affected by harvesting operations. Variable retention harvesting (VRH) increases forest structure heterogeneity in managed stands and decreases blowdown damages. The objective of this study was to characterize blowdown in Nothofagus pumilio forests managed with VRH in Southern Patagonia (Argentina). We analyzed long-term plots and one area affected by a windstorm after harvesting (exposure to winds and influence of retention patches) using univariate analyses. We found a differential impact in retention patches compared to dispersed retention after a windstorm considering aspect and distance to edge (e.g., blowdown trees: F = 6.64, p < 0.001). The aspect in retention patches presented few structural differences before the windstorm (e.g., tree diameter: F = 3.92, p = 0.014) but was not greatly influenced by the received damage after the windstorm. In long-term plots, we found that aspect and location in patches (distance to edge) determined the tree stability. We also found differences in wind damage considering retention level and design (e.g., aggregates and dispersed retention vs. aggregates and clear-cuts). We conclude that VRH increased the heterogeneity in harvested areas, where retention patches presented greater resilience in confronting extreme climate events and decreased recurrent wind exposure impacts in the long term. We found the marginal influence of aspect in the retention patches despite dominant winds and damages received by remnant trees during harvesting.